What's it all worth? : a qualitative study on what motivates women in low-paying jobs in Finland - Parviainen, Essi (2017)
The concept of work motivation has received increased attention in the management literature during the past decades, and the interest continues well into today’s management practices and related research. This should be the case, as motivated employees can be considered as the most valuable resources a company can have. Through exploratory research design, qualitative research strategy and qualitative thematic analysis of the data, this study aims to provide insights to what motivates women employed in low-paying jobs in Finland. Data collection was conducted through semi-structured interviews of 14 women who are working in jobs considered as low-paying. From the data, three overarching themes relating to factors that contribute towards women’s motivation could be found. The data suggests that quality of work, appreciation and personal development are the aspects that contribute the most to women’s work motivation. Moreover, it was discovered that for most of the participants’, money is not among the primary sources of work motivation. Instead, it was revealed that pay fades into the background when other motivating aspects are fulfilled. The themes were analyzed with the help of previous research, followed by presentation of eight distinct conclusions relating to what motivates women in low- paying jobs. After this, managerial recommendations were made based on the analysis and conclusions of the research. Finally, limitations of the study, along with further research opportunities and quality criteria were discussed. Altogether, the findings of the study offer new viewpoints on the phenomenon of women’s work motivation in low-paying jobs.